2016
DOI: 10.1108/jmtm-06-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing sources, key concerns and critical factors for manufacturing flexibility adoption

Abstract: Purpose – The purpose of this paper is to investigate factors influencing manufacturing flexibility adoption and simultaneously explores some of the key issues prevailing in manufacturing flexibility adoption in Indian context. The study also stratifies critical factors for successful manufacturing flexibility adoption. Design/methodology/approach – Using exploratory sequential design, a series of focus group interviews were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 46 publications
3
64
0
1
Order By: Relevance
“…Although most of the industries in India are desperate to increase their production rate, they are reluctant to make technological changes [29,30]. On investigation, it was identified that most of the manufacturing units in India are small and medium industries (SMEs), which have inadequate financial support.…”
Section: Ergonomics Problemsmentioning
confidence: 99%
“…Although most of the industries in India are desperate to increase their production rate, they are reluctant to make technological changes [29,30]. On investigation, it was identified that most of the manufacturing units in India are small and medium industries (SMEs), which have inadequate financial support.…”
Section: Ergonomics Problemsmentioning
confidence: 99%
“…Como resultado de sua natureza multidimensional, a flexibilidade não é genérica e deve ser cuidadosamente justificada, planejada e gerida, de forma a ser bem sucedida na sua implementação e gerar os resultados esperados (BEACH et al, 2000). Sua implementação não demanda, necessariamente, requisitos tecnológicos (MISHRA et al, 2016).…”
Section: Iiiiii Motivos Pelo Quais As Empresas Demandam Flexibilidaunclassified
“…First, the study does a confirmatory study by applying a covariance-based structural equation modeling (SEM) to test and verify the enablers of volume flexibility and product-mix flexibility. Thus, the use of SEM adopts a confirmatory rather than an exploratory approach to test and confirm multivariate causal relationships between enablers and flexibilities; second, unlike previous studies (Mishra et al , 2016), this study expands manufacturing flexibility into volume flexibility and product-mix flexibility rather than considering these flexibilities as a composite manufacturing flexibility latent constructs; thus this study empirically tests and verifies the enablers of volume flexibility and product-mix flexibility in firms; third, in addition to empirically investigating the enablers of volume flexibility and product-mix flexibility, this study measures the influence of these flexibilities on operational performance. This helps in avoiding the drawbacks associated with prior studies (Perez-Perez et al , 2018), which have primarily focused on financial measures; fourth, unlike the majority of earlier studies where the focus was on advanced economies (Mishra et al , 2014), the study indicates the importance of volume flexibility and product-mix flexibility across industries in India.…”
Section: Introductionmentioning
confidence: 99%